Concerted effort required to make NKRA on living cost a success - Borneo Post, (KK) (Borneo Post (KK), 2011)
KUALA LUMPUR: While the addition of a National Key Result Area (NKRA) to deal with living cost reflected the government seriousness in improving the quality of life it will only succeed with the involvement of the people.